Firstborn microcrystallization method to prepare nanocapsules containing artesunate - Xin-Cai Xiao (Dove Medical Press, 2010)
Xin-Cai Xiao, Zong-Guo HongSchool of Pharmacy, South-Central University for Nationalities, Wuhan, 430074, ChinaAbstract: We developed a novel method to prepare nanocapsules. A solute often crystallizes when its solubility alters from one solvent to another, and its firstborn crystals are used as templates to prepare nanocapsules for the first time, which is called firstborn microcrystallization method. By using this method, the maximum diameter of the nanocapsules including artesunate is about 76 nm, and wrapping state is well. One important advantage of our method is that the preparation of the nanocapsules operates easily and is a one-time process with no other cumbersome processes necessary, therefore avoiding secondary pollution. The proposed method provides a new route to prepare monodisperse nanocapsules to increase bioavailability of hydrophobic solutes.Keywords: firstborn microcrystallization method, nanocapsules, artesunate